The Effect of Differences of Live Feed on The Growth And Survival of Redtail Catfish (Hemibagrus Nemurus) Larvae. - Rizal Akbar Hutagalung; Farid Mudlofdar; Ridwan Salim (Journal of Aquaculture Science, 2021)
Baung fish is one of the local fish in West Kalimantan which has high economic value. One of the problems that arise in the maintenance of baung fish larvae is the low survival and growth rate, the most strategic solution is to determine the right type of feed according to the feeding habits of the baung fish larvae. The purpose of this study was to obtain the type of natural food that was most effective in rearing the larvae of fish. The research design used a completely randomized design (CRD) with 4 treatments and 3 repetitions. Treatment types of natural feed used in this study were Artemia (A), Water Fleas (B), Silkworms (C) and Pellet Flour (D), and arranged randomly. The results of the research through analysis of variance (Anova) show that all treatments can have a significant effect on the absolute length growth rate variable and the survival rate variable. Based on Tukey's further test, the treatment that had the best effect on the growth rate of absolute length was treatment C, namely 9.20 ± cm, while the treatment with the highest effect on survival rate was treatment A which was 98.8Keywords: Natural Feed, Baung Fish, Growth, Survival